(untitled) (Acta Scientiarum. Biological Sciences, 2013)
Despite the ecological importance of bromeliads, the basic knowledge about the physiological aspects in some species is poorly understood. The aim of this study was to physiologically characterize the species Nidularium campo-alegrense Leme and Aechmea ornata Baker to contribute to a better understanding of their metabolic processes. From mature leaves of bromeliads N. campo-alegrense and A. ornata held at the Agricultural Sciences Center of the Federal University of Santa Catarina, it was quantified photosynthetic pigments, carbohydrates and starch, and determined stomata and trichome density. The chlorophyll and carotenoids content did not differ significantly between species. However, the total carbohydrates content of A. ornata (3.2 mg g-1 FM) was significantly higher than N. campo-alegrense, but with similar starch content (1.7 mg g-1 FM). Both species present hypostomatic leaves, with more trichomes in the species A. ornata. This information provides the groundwork for future studies on the biochemical mechanisms related to their photosynthetic process, contributing in establishing strategies for the conservation and propagation of these species.